2021
DOI: 10.1002/ijc.33746
|View full text |Cite
|
Sign up to set email alerts
|

Avelumab expanded access program in metastatic Merkel cell carcinoma: Efficacy and safety findings from patients in Europe and the Middle East

Abstract: Incidence rates of Merkel cell carcinoma (MCC), an uncommon skin cancer with an aggressive disease course, have increased in recent decades. Limited treatment options are available for patients with metastatic MCC (mMCC). Avelumab, an anti-programmed cell death-ligand 1 monoclonal antibody, became the first approved

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Again the most common AEs were infusion-related reaction reported in 2.4% of cases and pyrexia in next 2.1% of patients. No new toxicities were observed in this study [27]. Moreover in our real world study we enrolled 161 MCC patients who were treated with curative intent.…”
Section: Avelumab -Expanded Access Programmentioning
confidence: 79%
“…Again the most common AEs were infusion-related reaction reported in 2.4% of cases and pyrexia in next 2.1% of patients. No new toxicities were observed in this study [27]. Moreover in our real world study we enrolled 161 MCC patients who were treated with curative intent.…”
Section: Avelumab -Expanded Access Programmentioning
confidence: 79%
“…[6][7][8][9][10] While incidence data in Latin America and parts of Asia are scarce, multiple studies have shown that fair-skinned individuals have twice the risk when compared to the general population. 7,[11][12][13][14] Current studies have examined a wide range of populations, including the US, Latin America, the Netherlands, Italy, Israel, and the Middle East. A significant portion of these studies are supported by expanded access programs (EAPs).…”
Section: Demographicsmentioning
confidence: 99%
“…EAPs allow for the compassionate use of avelumab in patients in whom multiple chemotherapies have failed, surgery is not an option, and clinical trials are not accessible (secondary to immunosuppressed status). 11 The incidence of MCC peaks in the eighth decade of life likely due to higher cumulative UV radiation exposure and immunosenescence, both of which are risk factors for MCC. 15,16 The median age range in real-world studies ranges from 67.1 to 78 years.…”
Section: Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the global avelumab program expanded access, which was designed to provide the compassionate use of avelumab prior to approval and led to similar response rates. The main treatment-related adverse events reported were infusion-related reactions and pyrexia [ 101 , 102 ].…”
Section: The Role Of Immunotherapy In Non-melanoma Skin Cancermentioning
confidence: 99%